From the Original Text to the Italian Adaptation: “Italianità” in “Another Simple Favor” (2025) - Corrizzato, Sara (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The article explores how the concept of italianità, i.e., the sense of Italian identity and cultural belonging, is constructed and reinforced in the Italian dubbed version of Another Simple Favor (2025), the sequel to Paul Feig’s A Simple Favor (2018). Drawing on the framework of audiovisual translation studies, the paper examines how linguistic and cultural choices in dubbing affect the representation of characters and their identities. While dubbing traditionally tends to neutralize linguistic variation to enhance comprehension by the audience, this study reveals the opposite: the Italian version of the film amplifies cultural specificity through deliberate localization. Using a qualitative, comparative methodology, the analysis includes selected excerpts from both the original English version and its Italian adaptation, focusing on the speech of the main characters. The analysis identifies two main strategies for conveying italianità: the insertion of Italian (or dialectal) lines in the English script to mark intimacy or cultural embeddedness, and the extensive use of Neapolitan dialect in the dubbed version to localize characters within a recognizable Italian context. These linguistic choices enrich the film’s cultural references but also risk introducing stereotypes associated with Southern Italian linguistic-cultural background. By contrasting the cosmopolitan, multilingual portrayal of characters in the original film with their more regionally defined counterparts in the dubbed version, the study highlights how dubbing becomes an active agent of identity negotiation.
Keywords: audiovisual translation; Italian dubbing; dialect